Studies on Schismatoglottideae (Araceae) of Borneo XXXXIX – Schismatoglottis antu, a new species allied to Schismatoglottis gui - Wong, Sin Yeng; Boyce, P.C (International Aroid Society, Inc., 2015)
Ongoing fieldwork in the north western part of the “Heart of Borneo” has revealed a new species of Schismatoglottis allied to the recently described and enigmatic Schismatoglottis gui and S. camera-lucida. This novelty is here described and illustrated as Schismatoglottis antu S. Y. Wong & P. C. Boyce, sp. nov.